Biostratigraphyand Paleoenvironments of Benthic Foraminifera From Lower Part of the Damlouk Member, Western Desert, Iraq - Al-Qayim, Basim; Ghafor, Imad (Iraqi Journal of Science, 2022)
Age and paleoenvironment of part of the Damlouk Member, Ratga Formation from a surface section in the Iraqi Western Desert are investigated. Twenty-nine species of Larger Benthic Foraminifera (LBF) belonging to 13 genera are recognized from the studied section. The LBF assemblage is dominated by the following groups, Nummulites, Alveolina, Rotalia, and Lockhartia. Two species of corals with fragments of bryozoan, red algae and mollusca had also been identified. The palaeontological investigation aimed at identification of LBF assemblages to evaluate their abundance and distribution with respect to sedimentary environment and to determine its age. Based on the recognized Larger Benthic Foraminifera of the studied part of the Damlouk Member, it is subdivided into two biozones: Nummulites gizhensis -Nummulites moculatus Assemblage Zone and Assilina spira- Lokharatia hunti Concurrent Range Zone. Both biozones suggest a Middle - Late Lutetian to Early Bartonian age. The LBF are concentrated around shallow marine carbonate bank-controlled limestone unit and the associated ramp facies. Two basic environmentally significant assemblages were recognized based on the vertical distribution and the relative abundance of the LBF. The Nummulite bank assemblage is characterized by lensoidal and robust Nummulites of different species. The other group is the fore-bank assemblage which shows relatively higher diversity, including flat LBF such as: Nummulite, Assilina, Lockhartia, Heterostigina and Operculina. The third back-bank assemblage is not well presented in the studied section, shows the limited distribution, and is considered part of the back-bank lagoon facies. This group is characterized by the occurrence of Alveolina and other imperforated forams. The recognized assemblages represent the transition from inner to middle ramp facies with a water depth not exceeding 50m in relatively low energy conditions.